ANALISIS PENENTUAN HARGA POKOK PRODUKSI DENGAN MENGGUNAKAN METODE FULL COSTING SEBAGAI DASAR PENETAPAN HARGA JUAL PADA USAHA MIKRO GOLLA KAMBU TEPPO MAMA RINA - Yusuf, Muh. Silmi Kaffa; Rijal, Abdul; Idris, Hariany (LPPM Universitas Bina Bangsa, 2024)
This research aims to analyze the determination of cost of production using the full costing method as the basis for setting selling prices at the micro business Golla Kambu Teppo Mama Rina. The focus of this research is on the cost of production using the full costing method and the selling price. Data collection techniques were conducted using triangulation techniques, namely observation, interviews, and documentation. Data analysis was carried out using qualitative descriptive analysis. The results of this study indicate that the calculation of the cost of production based on the full costing method results in higher costs compared to the calculation by Golla Kambu Teppo Mama Rina. The cost of production obtained according to Golla Kambu's business is IDR 29.778 per package, while that obtained by the researcher is IDR 30.407 per package. The selling price determined by Golla Kambu Teppo Mama Rina is IDR 32,000 per package, whereas that obtained by the researcher is IDR 36.487 per package. This difference occurs because Golla Kambu Teppo Mama Rina does not account for all costs (factory overhead costs) incurred in the production process in detail